The concept of smart contract from a civil law perspective: An analytical study - Mohamed, Abdelrazek Wahba Sayed Ahmed (Journal of Economic, Administrative and Legal Sciences, 2021)
Contract law is the most developed area to confront modern technologies, including smart contracts, which may raise some legal problems when applied in practice due to the automatic implementation mechanism. Therefore, the research aimed at presenting the concept of a smart contract and its origin, and identifying its legal characteristics and nature, along with an indication of the problems that it could raise. We have concluded with a set of results, including: There is no unified definition of a smart contract that has the feature of automatic implementation of the terms agreed upon by the parties through computer programs. Hence, it is not possible to amend the contract in case of emergency circumstances or to cancel it in case of force majeure. Moreover, it is difficult to determine the necessary eligibility of the contracting parties, in addition to the difficulty of interpreting the smart contract due to its writing in a programming language that the judges and lawyers cannot understand which leads the courts to seek the assistance of experts to interpret it. That is why we recommended the necessity of developing unified legislation to regulate the smart contract, and establishing centers for training judges to enable them to understand the language in which this contract is written to interpret it in the event of a dispute between its parties. In addition to modifying the block chain platform to make the smart contract flexible and subject to change similar to traditional contracts.
Keywords: smart contract; contracting capacity; force majeure; emergency circumstances; contract interpretation